Foreign reserves management subject to a policy objective - Joachim Coche; Matti Koivu; Ken Nyholm; Vesa Poikonen (European Central Bank (ECB), 2006)
This paper studies the implications of introducing an explicit policy objective to the management of foreign reserves at a central bank. A dynamic model is developed which links together reserves management and the exchange rate by foreign exchange interventions. The exchange rate is modelled as a mean-reverting autoregressive process incorporating a linear response to interventions. The premise is that it is the objective of the central bank to prevent undervaluation of its currency. Given this objective, the model is formulated in a one- and a multi-period setting and solved to find the optimal asset allocation. The results show that asset allocation can significantly help in achieving the desired policy objective.
Keywords: G11; F31; 330; exchange rate modelling; foreign exchange intervention; Foreign reserves management; optimal asset allocation; Währungsreserven; Zentralbank; Portfolio-Management; Theorie